Medicolegal Penggunaan Kadaver Manusia Untuk Bedah Anatomi Medis dan Transplantasi Organ: Medicolegal Use of Human Cadavers for Medical Anatomical Surgery and Organ Transplantation - Muhni, Afif; Basri, Muhammad; Kadir, Zul Khaidir (Magister Ilmu Hukum - Universitas Hang Tuah, 2025)
This study examines the legal and ethical position in the use of human cadavers in Indonesia after anatomical cadaver surgery an organ transplantation, with a focus on the legal, ethical and regulatory aspects governing the use of cadavers for the purposes of medical education and research. In the context of health law, it is important to understand how regulations in Indonesia ensure the use of cadavers in accordance with applicable legal and ethical norms. This research is a normative-empirical study and uses a qualitative approach with document analysis methods, including laws, government regulations, comparation regulation and related literature. The results of this study obtained a conclusion on the need for regulation regarding the maximum limit on the use of human cadavers so that human rights, ethics and values that live in society and also religious values do not conflict with the objectives in the development of science in the field of health, as well as the need for renewal of data collection and government participation in this case the Ministry of Health to record every ownership of human cadavers with the aim of minimizing the illegal trade and transplantation human organs.